2016
DOI: 10.1182/blood-2016-01-690743
|View full text |Cite
|
Sign up to set email alerts
|

Dependence on glutamine uptake and glutamine addiction characterize myeloma cells: a new attractive target

Abstract: Key Points• Myeloma cells produce ammonium in the presence of glutamine, showing high glutaminase and low glutamine synthetase expression.• Myeloma cells show high expression of glutamine transporters and inhibition of ASCT2 transporter hinders myeloma growth.The importance of glutamine (Gln) metabolism in multiple myeloma (MM) cells and its potential role as a therapeutic target are still unknown, although it has been reported that human myeloma cell lines (HMCLs) are highly sensitive to Gln depletion. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
156
1
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(165 citation statements)
references
References 58 publications
1
156
1
3
Order By: Relevance
“…While previous studies investigating the effects of CB-839 have demonstrated similar activity between CB-839 treatment and glutamine deprivation in cancer cells [13, 26, 42], our study differs fundamentally in that we were specifically investigating the activity of CB-839 in combination with PIs. We speculate that CB-839 induces a specific set of molecular effects that diverges from those induced by withdrawing all or part of glutamine from cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies investigating the effects of CB-839 have demonstrated similar activity between CB-839 treatment and glutamine deprivation in cancer cells [13, 26, 42], our study differs fundamentally in that we were specifically investigating the activity of CB-839 in combination with PIs. We speculate that CB-839 induces a specific set of molecular effects that diverges from those induced by withdrawing all or part of glutamine from cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that MM cells lack expression of glutamine synthetase and display an increased expression of glutaminase 1 (GLS1), suggesting that these cells rely exclusively on extracellular glutamine for cellular energy [13]. GLS catalyzes the conversion of glutamine to glutamate, which supports redox balance through glutathione biosynthesis, and serves as a major substrate for the mitochondrial tricarboxylic acid (TCA) cycle [1416].…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, overexpression of the transcription factor c-MYC is believed to drive progression of MGUS and SMM to MM (8). c-MYC also regulates glutamine metabolism by increasing glutamine anaplerosis into the TCA cycle of mitochondria (9), which is vital in clonal PCs from human myeloma cell lines (HMCLs) (10). 2-Hydroxyglutarate (2-HG), an oncometabolite derived from α-ketoglutarate in the TCA cycle, has been associated with epigenetic modifications causing tumorigenesis in cancers associated with IDH1/2 mutations such as acute myeloid leukemia (11,12) and glioblastoma (13).…”
Section: Introductionmentioning
confidence: 99%
“…Tumor cell proliferation is susceptible to alterations in microenvironment pH (Bolzoni et al, 2016). To explore causes of reduced pH, we measured its lactate concentration, because lactate is a major source of acidity in cell metabolism (Seheult et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The glutamate dehydrogenase1 ( GDH ) encodes a trifunctional protein that is associated with the enzymatic activities of glutaminolysis (Koo and Yoon, 2015). The solute carrier family 1 member 5 ( SLC1A5 ) is related to glutamine uptake (Bolzoni et al, 2016). The solute carrier family 7 member 11 ( SLC7A11 ) is responsible for glutamate release in glutaminolysis (Kalivas, 2009).…”
Section: Introductionmentioning
confidence: 99%